VILLAGE FINANCIAL MANAGEMENT IN GAMPONG BLANG MAKMUR KUALA BATEE DISTRICT SOUTHWEST ACEH REGENCY - Syarkawi Syarkawi; Hendri Koeswara; Desna Aromatica (Universitas Negeri Medan, 2023)
The birth of Law Number 6 of 2014 concerning Villages became a milestone in changing the paradigm about villages. The village is no longer an object but has become a subject of development and has the authority to manage its own finances. As a consequence of this authority, financing or finance is a very essential factor in supporting the implementation of village autonomy or gampong. The handover of authority to gampong raises great demands on financial management by the community against the Gampong Government. These demands must be responded to by making changes in gampong financial management. This study aims to determine how financial management in Gampong Blang Makmur, Kuala Batee District, based on Permendagri Number 20 of 2018 concerning Village Financial Management. With the research method carried out using a type of descriptive qualitative research that seeks to tell the solution of problems that occur now based on data in which there are efforts to describe, record, analyze and interpret conditions that are now occurring in other words descriptive research aims to obtain information about the current situation with data collection techniques in the form of interviews, ducumentation and observation. Gampong Blang Makmur's financial management has been carried out properly in accordance with the stages and principles in village financial management in accordance with the mandate of Permendagri Number 20 of 2018 concerning Village Financial Management. However, there are several shortcomings and weaknesses in the implementation at each stage, including: The determination of the Gampong Blang Makmur APBG is not in accordance with the established schedule; Inadequate apparatus human resources in gampong financial management, to delayed and untimely gampong financial management accountability reports. On the other hand, gampong financial management is not as autonomous as imagined, most of gampong's finances are guided to implement district priority programs.